2021
DOI: 10.1037/ccp0000628
|View full text |Cite
|
Sign up to set email alerts
|

Agency and alliance as change factors in psychotherapy.

Abstract: Objective: This study examined the reciprocal effects between therapeutic agency, working alliance, and symptoms during psychotherapy. We aimed to predict symptom improvement by previous changes in either agency or alliance. In addition, we examined whether alliance development was predicted by previous changes in agency. Method: A sample of 386 patients in psychodynamic outpatient psychotherapy answered the Therapeutic Agency Inventory (TAI), the Working Alliance Inventory-SR (WAI-SR), and the Symptom Checkli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 62 publications
4
26
0
1
Order By: Relevance
“…Therapeutic agency has been found to be related to lower psychological distress, lower depression scores, and better therapy outcomes even when controlling for baseline distress (Huber et al, 2019). Furthermore, positive changes in agency predicted subsequent symptom improvement in patients (n = 386) in psychodynamic outpatient psychotherapy (Huber et al, 2021).…”
Section: Continuity With Prior Empirical Researchmentioning
confidence: 97%
“…Therapeutic agency has been found to be related to lower psychological distress, lower depression scores, and better therapy outcomes even when controlling for baseline distress (Huber et al, 2019). Furthermore, positive changes in agency predicted subsequent symptom improvement in patients (n = 386) in psychodynamic outpatient psychotherapy (Huber et al, 2021).…”
Section: Continuity With Prior Empirical Researchmentioning
confidence: 97%
“…In a psychometric study on the WAI-SR [59], the average WAI-SR score for in-person outpatient therapy in their sample of 88 patients was reported as 3.8 (SD = 0.63). More recently, in a previous study on a 20-session treatment of an in-person outpatient sample (N= 386), in which therapeutic agency was also assessed, the average WAI-SR ranged from 3.65 to 3.88 (SD ranging from 0.70-0.77) depending on the phase of treatment [56]. Although no studies reporting on the patient-reported WAI-SR in online therapy during COVID appear to have been published, therapist-reported WAI-SRT scores during online therapy during COVID suggest similar ratings of the working alliance (M = 4.09, SD = 0.48; [60].…”
Section: Methodsmentioning
confidence: 99%
“…It is thought that a low sense of agency may exacerbate relationship difficulties, also within the therapist-patient dyad [52]. Patients' sense of agency may manifest within psychotherapy sessions as their contribution to the therapy process, openness, expressiveness, cooperativeness, autonomy, contribution to the therapeutic bond, active collaboration, and interactive collaboration with the therapist [54], and has been associated with a stronger working alliance [49,55,56].…”
Section: Patients' Experiences Of the Collaborative Process In Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Es interessiert nicht mehr nur, dass die therapeutische Beziehung eine offensichtlich wichtige Komponente jeder Therapie ist. Sondern es wird gefragt, wie die Kausalitäten sind, welches die Wirkmechanismen sind und was wir für die Gestaltung der therapeutischen Beziehung lernen können [38].…”
Section: Therapie(prozess)forschungunclassified